2018
DOI: 10.1371/journal.pone.0199130
|View full text |Cite|
|
Sign up to set email alerts
|

A novel epigenetic modulating agent sensitizes pancreatic cells to a chemotherapy agent

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is expected to be the second leading cause of cancer mortality by 2030. PDAC remains resistant to the majority of systemic chemotherapies. In this paper, we explore if epigenetic sensitization can improve chemotherapy response in PDAC. Multiple PDAC cell lines were tested with serial concentrations of the epigenetic modulators 5-azacitidine (Aza) and guadecitabine (SGI-110). Guadecitabine was effective at inhibiting the expression of DNA Methyltransferase 1 (DNMT1) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…However, the effect of DNMT1/miR-29b-3p on cell apoptosis and cycle was not investigated in the present study. Based on previous research, DNMT1 siRNA induces a significant cell viability decrease, leads to a G2-phase block and cell apoptosis in pancreatic cancer (10,52), indicating that this axis may promote cell survival. Further study will focus on this aspect.…”
Section: Discussionmentioning
confidence: 84%
“…However, the effect of DNMT1/miR-29b-3p on cell apoptosis and cycle was not investigated in the present study. Based on previous research, DNMT1 siRNA induces a significant cell viability decrease, leads to a G2-phase block and cell apoptosis in pancreatic cancer (10,52), indicating that this axis may promote cell survival. Further study will focus on this aspect.…”
Section: Discussionmentioning
confidence: 84%
“…In pancreatic cancer cell lines with low DNMT1 expression, the DNMT inhibitor decitabine depletes DNMT1 and exerts anti-tumor effects [ 25 ]. While guadecitabine sensitizes pancreatic cancer cells to chemotherapeutic agents [ 29 ], there is only one phase I study evaluating the anti-tumor effect of DNMT inhibitor on pancreatic cancer [ 30 ].…”
Section: Dna Methylationmentioning
confidence: 99%
“…However, zebularine drives PDAC stem cells to a more proliferative phenotype with increased sensitivity to current chemotherapies. A recent study (35) also showed an improvement in the response of MIA PaCa-2 and PANC-1 cell lines to irinotecan after sensitization with guadecitabine (SGI-110), a next generation epigenetic modulator with a longer half-life and better tolerability than 5-AZA (36). Nevertheless, data obtained from modifying DNA methylation patterns in cell lines may not reflect the heterogeneity present among patients and so, its extrapolation to clinics is uncertain.…”
Section: The Epigenetic Landscape Underlying Pdac As a Target For Patmentioning
confidence: 99%